2014
DOI: 10.1684/ejd.2013.2258
|View full text |Cite
|
Sign up to set email alerts
|

The European Standard Series and its additions: are they of any use in 2013?

Abstract: This study has two purposes: -to know whether the European standard series is still the key reference when it comes to contact dermatitis, i.e., are its components still the most frequently involved allergens in contact dermatitis nowadays? -to assess the results of the European standard series among French and Belgian dermatologists/allergists as, so far, most of them have failed to provide statistical data within the European community of allergists/dermatologists. 18 participants from 2 dermatology and alle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 32 publications
3
6
0
2
Order By: Relevance
“…The high proportion of women in our study (90%) is similar to the percentage (70‐90%) reported in previous studies in other countries . It is higher than the 70% proportion of females in French patients patch tested for eczema with various localizations . This difference is usually attributed to higher cosmetic use among women, which is also supported by our study, in which 67.9% of the EACD cases were attributable to cosmetics.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The high proportion of women in our study (90%) is similar to the percentage (70‐90%) reported in previous studies in other countries . It is higher than the 70% proportion of females in French patients patch tested for eczema with various localizations . This difference is usually attributed to higher cosmetic use among women, which is also supported by our study, in which 67.9% of the EACD cases were attributable to cosmetics.…”
Section: Discussionsupporting
confidence: 90%
“…The most frequent allergens of current relevance in our study were MI, fragrance mix I, nickel sulfate, hydroxyperoxides of linalool and limonene, and M. pereirae. These allergens are the same as those reported most frequently in the population patch tested for eczema with various localizations . The very high prevalence of positive test reactions to MI (10.2%) can be explained by the worldwide outbreak of contact sensitization to this allergen, in which the eyelids are a classic localization, but the mixture MI/methylchloroisothiazolinone was already recognized as a main allergen in EACD before the MI sensitization outbreak .…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Die Anpassung einer Standardreihe an lokale Gegebenheiten ist in Abständen erforderlich . Die aktuelle Standardreihe und weitere Testreihen der DKG sind der Homepage der DKG (dkg.ivdk.org/) zu entnehmen.…”
Section: Auswahl Und Applikation Von Testsubstanzen (Inkl Testung MIunclassified
“…Therefore, flexibility is the rule, and adaptations are constantly needed, following environmental changes. Some allergens can become obsolete, whereas others are emerging (20).…”
Section: The Baseline (Standard) Seriesmentioning
confidence: 99%